2014
DOI: 10.1206/3813.1
|View full text |Cite
|
Sign up to set email alerts
|

Systematics ofVampyressa melissaThomas, 1926 (Chiroptera: Phyllostomidae), with Descriptions of Two New Species ofVampyressa

Abstract: Vampyressa melissa is a poorly known phyllostomid bat listed as vulnerable by the Inter¬ national Union for Conservation of Nature (IUCN). Since its description in 1926, fewer than 40 V. melissa have been reported in the literature, and less than half of these may have been correctly identified. During revisionary studies of Vampyressa, we uncovered two previously unrecognized species related to V. melissa, all associated with higher elevation habitats (>1400 m), one from the Andes of Colombia (Vampyressa sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
(28 reference statements)
0
22
0
3
Order By: Relevance
“…; Tavares et al . ). The evidence obtained in the present study revealed that Cynomops may be a complex of six to eight species.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Tavares et al . ). The evidence obtained in the present study revealed that Cynomops may be a complex of six to eight species.…”
Section: Discussionmentioning
confidence: 97%
“…We used 39 discrete morphological characters, including 30 modified from Velazco (), Giannini & Simmons (), Tavares (), Tavares et al . (), Gregorin () and Gregorin & Cirranello (). A matrix containing all morphological characters used and a character description list is provided in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Of these characters, 160 were coded for four fossil taxa currently known for Stenodermatinae. These characters were based on, but not restricted to, those defined by Wetterer, Rockman, and Simmons (2000); Tavares (2008); Tavares and Mancina (2008); Tavares, Gardner, Ram ırez-Chaves, and Velazco (2014). The morphological matrix and character states were compiled using MacClade version 4.08 (Maddison & Maddison, 2003).…”
Section: Morphological Datamentioning
confidence: 99%
“…In the genus Vampyressa there is a craniodental character, a small cusp in the lingual border of the longitudinal sulcus on posterior crown of upper canines (Tavares et al 2014), but in the V. thyone specimens examined in the MZFC-M the accessory cusps seem to be more developed in males than in females. Nevertheless, in the new specimen the accessory cusp is even more developed than in the other males.…”
Section: Resultsmentioning
confidence: 97%
“…The yellow-eared bats of the genus Vampyressa Wagner, 1843 consist of five different species, two of them recently described (Burgin et al 2018). These bats are considered primarily or exclusively frugivorous, though little is known of their feeding habitats or ecology (Tavares et al 2014). The distribution of this genus includes the Neotropical region, from Argentina to Mexico (Lim et al 2003).…”
Section: Introductionmentioning
confidence: 99%